Kualitas Pelayanan Publik Bidang Administrasi Kependudukan pada Program Paket Layanan (PAKLAY) Satu Hari Jadi di Kantor Desa Gaum, Kecamatan Tasikmadu, Kabupaten Karanganyar - Widyantoro Yuliatmojo; Anita Tri Utami; Nindita Pramuktisari; Roni Prihanto (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
Gaum Village, located in Karanganyar Regency, actively administers public services in the field of population administration. To cut bureaucratic red tape, the village government implemented an innovative "one-day service" initiative called the Paklay Program. However, operational bottlenecks, infrastructure limitations, and community grievances still present challenges in its execution. This study applied a qualitative descriptive method, selecting key informants through a purposive sampling technique. Primary insights were collected directly through structured interviews, supplemented by documentation studies. For data examination, a qualitative framework consisting of three interactive phases—data reduction, data display, and conclusion drawing—was utilized, with data validity verified through triangulation. The empirical evidence demonstrates that the service quality at the Gaum Village Office has successfully reached a competent and satisfactory standard. This achievement is reflected in the favorable scores across all evaluated service quality dimensions (tangible, reliability, responsiveness, assurance, and empathy). The primary strengths of the program lie in the swift processing time, administrative precision, and responsive complaint handling. Conversely, the main structural drawbacks center on inadequate physical waiting room facilities, periodic internet connectivity issues, and a literacy gap regarding the digitized procedures among elderly residents. Ultimately, this study concludes that the administrative services offered through the Paklay program have successfully enhanced public service delivery, though tactical improvements in infrastructure and inclusive socialization are strictly required for optimal outcomes.